PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA KARYAWAN RUMAH SAKIT DAERAH ARGAMAKMUR BENGKULU UTARA - Trio Budi Setyawan; Sri Ekowati; Ratnawili Ratnawili; Ade Tiara Yulinda (UM. Bengkulu, 2021)
This study aims to know the effect of competence and motivation on the performance of employees of ArgaMakmur Hospital, North Bengkulu. The object of this research is the employees of ArgaMakmur Hospital North Bengkulu, with the sampling method in this research is the total sampling method. The number of respondents in this study were 338 people. Data collection method in this study used questionnaires and observations. The data analysis technique used is multiple linear regression, the coefficient of determination (R2), and hypothesis testing. By using research test data analysis techniques, it can be concluded that competence (X1) and motivation (X2) have a positive effect on employee performance (Y) of ArgaMakmur Hospital North Bengkulu, this is proven by the multiple linear regression equation Y = 5.947 + 0.536 (X_1 ) + 0.261 (X2). In the results of multiple linear regression analysis, it shows the magnitude of the effect of the competency (X1) and motivation (X2) variables is positive on employee performance (Y) at ArgaMakmur Hospital, North Bengkulu, which is shown by the value of Adjusted R2 is 0.522. This means that the magnitude of the effect of the competency (X1) and motivation (X2) variables in this study is only able to affect the employee performance variable (Y) by 52.2% and 47.8% which is affected by other variables that are not included in this study. With the results of the hypothesis test, the competence has a significant effect on employee performance with the results of the t-test value of 0.000 <0.05.Work motivation has a significant effect on employee performance, with the results of the t-test show the value of t-sig is 0.000 <0.05, and the competence and motivation for employee performance simultaneously have a significant effect on employee performance. This is proven by the f-test which shows the F-sig value of 0.000 <0.05.Â Â Keywords: Motivation, Working Discipline, Employees, Performance.